2021
DOI: 10.3389/fonc.2021.712554
|View full text |Cite
|
Sign up to set email alerts
|

A CT-Based Radiomics Nomogram Integrated With Clinic-Radiological Features for Preoperatively Predicting WHO/ISUP Grade of Clear Cell Renal Cell Carcinoma

Abstract: ObjectiveThis study aims to develop and validate a CT-based radiomics nomogram integrated with clinic-radiological factors for preoperatively differentiating high-grade from low-grade clear cell renal cell carcinomas (CCRCCs).Methods370 patients with complete clinical, pathological, and CT image data were enrolled in this retrospective study, and were randomly divided into training and testing sets with a 7:3 ratio. Radiomics features were extracted from nephrographic phase (NP) contrast-enhanced images, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…All four models have similar and excellent performance and detailed AUC values are respectively displayed in the graph, indicating the robust performance of quantitative features after LASSO selection. (20,21). In this retrospective study, using stacking ensemble machine learning methods, we achieved excellent diagnostic performance in discriminating benign CRLs from malignant CRLs, which outperformed the Bosniak classification system.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…All four models have similar and excellent performance and detailed AUC values are respectively displayed in the graph, indicating the robust performance of quantitative features after LASSO selection. (20,21). In this retrospective study, using stacking ensemble machine learning methods, we achieved excellent diagnostic performance in discriminating benign CRLs from malignant CRLs, which outperformed the Bosniak classification system.…”
Section: Discussionmentioning
confidence: 82%
“…Previous findings suggested that the progression of Bosniak IIF cystic renal masses was 4 years ( 19 ). The high-risk Bosniak CRL had a quick progression that required radical nephrectomy rather than inappropriate surgical procedures like renal cyst decortication ( 20 , 21 ). In this retrospective study, using stacking ensemble machine learning methods, we achieved excellent diagnostic performance in discriminating benign CRLs from malignant CRLs, which outperformed the Bosniak classification system.…”
Section: Discussionmentioning
confidence: 99%
“…According to prior research, the progression of Bosniak IIF cystic renal masses is four years, which indicates a four years follow-up is inevitable [ 25 ]. Rapid progression of the high-risk Bosniak CRL necessitates radical nephrectomy rather than ineffective surgical procedures like renal cyst decortication [ 26 , 27 ]. In this retrospective study, we employed a blending ensemble machine learning model to stratify malignant and benign CRLs in cystic renal masses, which outperformed the Bosniak classification system.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to radiomics feature extraction, to reduce feature variability, we performed the following image preprocessing steps, containing gray discretization, intensity normalization, and voxel resampling ( 29 ). Then, radiomics features were extracted from the second phase of DCE-MRI images through the open source PyRadiomics library.…”
Section: Methodsmentioning
confidence: 99%